2019
DOI: 10.1111/bcpt.13323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aripiprazole on circadian prolactin secretion related to pharmacogenetics in healthy volunteers

Abstract: Aripiprazole treatment in schizophrenic patients was previously associated with lower or normalized prolactin levels. Genetic variants in cytochrome P450 (CYP) (CYP2D6), dopamine receptor (DRD2, DRD3) and serotonin receptor (HTR2A, HTR2C) genes were previously associated with antipsychotic‐induced hyperprolactinaemia. Our aim was to evaluate whether aripiprazole affects prolactin secretion and its relationship with pharmacogenetics. Thirty‐one healthy volunteers receiving a 10‐mg single oral dose of aripiprazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…Prolactin levels decreased after changing the therapy from other SGAs-including OLA-to ARI [32]. Our previous study showed that a single dose of ARI mildly increases prolactin levels compared to the controls [13]. However, compared to OLA, no change was observed in prolactin levels after administration in the present study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Prolactin levels decreased after changing the therapy from other SGAs-including OLA-to ARI [32]. Our previous study showed that a single dose of ARI mildly increases prolactin levels compared to the controls [13]. However, compared to OLA, no change was observed in prolactin levels after administration in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Nevertheless, prolactin concentrations were not affected by DRD2 polymorphisms and CYP2D6 phenotype after ARI administration in patients with schizophrenia [12]. On the contrary, an association was found between prolactin levels and CYP2D6 phenotype and HTR2C polymorphisms in healthy volunteers [13].…”
Section: Introductionmentioning
confidence: 85%
“…Nevertheless, prolactin concentrations were not affected by DRD2 polymorphisms and CYP2D6 phenotype after ARI administration in schizophrenic patients 12 . On the contrary, an association was found between prolactin levels and CYP2D6 phenotype and HTR2C polymorphisms in healthy volunteers 13 .…”
Section: Introductionmentioning
confidence: 75%
“…Prolactin levels decreased after changing the therapy from other atypical antipsychoticsincluding OLA -to ARI 23 . Our previous study showed that a single dose of ARI mildly increases prolactin levels compared to the controls 13 . However, compared to OLA, no change was observed in prolactin levels after administration in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation